Spatial analysis of the risk for canine visceral leishmaniasis in an urban area in the State of Sergipe - Santos, N. A.F.; Silva-Junior, F. F.; Silva, F. B.R. [UNESP]; Tosta, C. D.; Moura, K. D.; Jeraldo, V. L.S.; Madi, R. R.; Pinto, M. C. [UNESP]; Melo, C. M. (FapUNIFESP (SciELO), 2023)
Visceral Leishmaniasis is included among the neglected tropical diseases, being directly related to conditions of social vulnerability, in urban environments, dogs act as important reservoirs. The aim of the study was to evaluate the distribution of dogs, related risk factors and identify of volatile organic compounds from infected dogs. Peripheral blood samples from 72 dogs were collected for detection using the ELISA test, in addition to hair samples for analysis by GC-MS. Of the evaluated dogs, 13 (18.05%/72) were reactive for canine VL, seven in Aracaju and six in Propriá. Factors related to vegetation, age, place where the dog stays and free access to the street, were associated with a greater chance of the dog becoming infected. Fifty-three compounds were identified from ten canine hair samples, among which 2-butoxyethanol, benzaldehyde, decane, 2-phenylacetaldehyde, nonan-1-ol, 2-phenoxyethanol, nonanoic acid, 8-heptadecene and eicosane were found in seropositive dogs for leishmaniasis. The guardian’s posture has been increasingly important, requiring more attention to the dog’s health and actions aimed at environmental management in an attempt to reduce cases of canine VL in the state. Even though the identified VOCs have not been associated with leishmanial infection, it is of great use for understanding canine hair substances.
Análise espacial do risco para leishmaniose visceral canina em área urbana do estado de Sergipe
Keywords: canine visceral leishmaniasis; epidemiology; GC-MS; NDVI